Discrete mathematics and its applications - Rosen, Kenneth H. (Boston : WCB/McGraw-Hill, 1999)
This text is designed for the sophomore/junior level introduction to discrete mathematics taken by students preparing for future coursework in areas such as math, computer science and engineering. Rosen has become a bestseller largely due to how effectively it addresses the main portion of the discrete market, which is typically characterized as the mid to upper level in rigor. The strength of Rosen's approach has been the effective balance of theory with relevant applications, as well as the overall comprehensive nature of the topic coverage.
Includes bibliographical references and index.
Keywords: Mathematics; Computing; Computer science -- Mathematics